EDUKASI PEMILAHAN SAMPAH DENGAN MEDIA INTERAKTIF PADA SISWA KELAS 1 SD NEGERI PENANGGUNGAN: WASTE SORTING EDUCATION WITH INTERACTIVE MEDIA FOR 1ST GRADE STUDENTS OF SD NEGERI PENANGGUNGAN - Safitri Nur Ramadhani; Aileena Solicitor Costa Rica El Chidtian (Pakis Journal Institute, 2023)
Waste problems are often encountered in the surrounding community. Penanggungan Village is one of the tourist villages located in Trawas District, Mojokerto Regency. Environmental cleanliness is certainly in the spotlight because many tourists visit the village. In minimizing littering, it is necessary to provide early education about waste sorting, especially for elementary school students. Through community service activities, Bina Desa Trawas of MBKM Universitas Pembangunan Nasional